Implementation of Reflective Learning Strategies to Improve Students' Comprehension Ability in Civics Lessons in Elementary Schools - Ainun Mardiah (Yayasan Zia Salsabila, 2023)
Reflective thinking is a student's ability to select knowledge that has been owned and stored in its memory to solve every problem it faces to achieve goals. This study aims to improve student learning outcomes by using a reflective learning model in Civics subjects. The subjects of this study were all 21 grade III students. While the object of this research is the results of student learning in Civics subjects with the theme